Molecular Detection of Salmonella pullorum from Poultry Ceca and Vaccine Preparation - Abed , Tariq khalil; Ali, Balqees Hassan (International Journal of Poultry Science, 2018)
Objective: Isolation of Salmonella pullorum (S. pullorum) from chicken ceca and confirmation by PCR after a trial to prepare a vaccine from this isolate by using the freezing and thawing method. Materials and Methods: A total of 69 samples were isolated from chicken ceca. Biochemical tests were performed and diagnoses were made. Twenty-one Salmonella positive samples were found, 12 of which were S. pullorum, which were confirmed by differential biochemical tests (glucose, sucrose, lactose, mannitol and maltose) and additionally confirmed by PCR. The second part of the study was to determine the LD50 of S. pullorum at doses up to 2×10–7 after isolate exposure to slow freezing and after thawing, which effected isolation effectiveness. The third part of the study included the 28 day a challenge-dose test. Results: Mortality in the control group (n = 15) was 20%, with clinical signs. On the third day of challenge via oral inoculation with S. pullorum (0.5 mL of 2×10–7 CFU mL–1), there were two cases of lameness that improved in the vaccinated group. Over 2-3 days, signs of respiratory symptoms were minimal and nonspecific, with animals in the control group showing a dull appearance, depressed activity and a loss of appetite. Non-significant signs were noted 5 days after experimental infection in the vaccinated group. Conclusion: The isolation and characterization of S. pullorum from infected blisters and attempts to prepare a vaccine using a freezing and thawing method showed protective results after the challenge test with the same isolated strain compared to results in non-vaccinated chickens.